2012
DOI: 10.1103/physreva.86.032306
|View full text |Cite
|
Sign up to set email alerts
|

Double-slit implementation of the minimal Deutsch algorithm

Abstract: We report an experimental implementation of the minimal Deutsch algorithm in an optical setting. In this version, a redundancy is removed from the most famous form of the algorithm. The original version involves manipulation of two qubits, while in its minimal version, only one qubit is used. Our qubit is encoded in the transversal spatial modes of a spontaneous parametric down-converted signal photon, with the aid of a double slit, with the idler photon playing a crucial role in creating a heralded single pho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In the simplest approach, this discretization is achieved when the photons are made to pass through an aperture with D slits which sets the qudit dimension [5]. Due to this simplicity, spatial qudits enables one to work in high dimensions without cumbersome optical setups and for that reason they have drawn interest for miscellaneous applications such as quantum information protocols [6], quantum games [7], quantum algorithms [8], and quantum key distribution [9]. Most of those applications has benefited from the recent developments on the control of spatial qudits based on the technology of electrically addressed spatial light modulators (SLMs).…”
Section: Introductionmentioning
confidence: 99%
“…In the simplest approach, this discretization is achieved when the photons are made to pass through an aperture with D slits which sets the qudit dimension [5]. Due to this simplicity, spatial qudits enables one to work in high dimensions without cumbersome optical setups and for that reason they have drawn interest for miscellaneous applications such as quantum information protocols [6], quantum games [7], quantum algorithms [8], and quantum key distribution [9]. Most of those applications has benefited from the recent developments on the control of spatial qudits based on the technology of electrically addressed spatial light modulators (SLMs).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of programmable spatial light modulators (SLM) has enhanced the potential for this encoding, providing advances ranging from automated state preparation [20] to automated state transformations [21]. In turn, these advances provided a fertile ground for many recent applications of these multipath qudits such as the demonstration of novel quantum tomographic techniques [22,23], quantum algorithms [24], entanglement characterization [25] and concentration [26], simulation of decoherence [27], quantum key distribution [28], state discrimination [29], and contextuality tests [30][31][32]. However, regarding the transformations (in which the final state is preserved), so far the operations implemented via SLMs have been restricted to diagonal ones in the ba-Typeset by REVT E X arXiv:1703.10752v1 [quant-ph] 31 Mar 2017 sis of which-path states.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that D entangled photons can be produced so as to produce interference fringes with period proportional to the de Broglie wavelength of the D-photon wave packet [12,23,25,26], which has been shown to be potentially useful for quantum lithography [27]. Additional experiments include spatial antibunching [20,21], fractional topological phase of entangled photons [28], tests of quantum complementarity [4][5][6]15], quantum contextuality [29], and quantum information protocols [30]. It is also possible to produce high-dimensional entangled photons using temporal wave packets [31,32].…”
Section: Introductionmentioning
confidence: 99%